Physico-Chemical and Biochemical Changes of Capsicum Annuum Var. Kulai During Development and Using Modified Atmosphere Packaging System - Wong, Mei Chee (2004)

(untitled)
The objective of this study is to determine the optimal hawesting stage for Capsicum annuum var. kulai. Capsicum annuum var. kulai was harvested weekly from day 21 to day 49 after anthesis and analysed for its physico chemical and biochemical changes during growth, maturation and ripening. Analysis were carried out at five stages: immature green (d 21), mature green (d 28), breaker (d 35), red (d 42) and ripen red (d 49). Physicochemical and biochemical parameters were analysed. They included determining of the fruit colour, weight loss, firmness, ethylene and carbon dioxide (C02) production, pigment contents, carotenoid contents, organic acids contents, sugars, starch, pectin, capsaisinoids contents, and cell wall degradative enzymes activities. This study also aims to determine the effects of Modified Atmosphere Packaging (MAP) in prolonging its shelf life. Experiments were carried out using packaging materials such as Pow Vinyl Chloride (PVC) cling wrap, Low Density Polyethylene (LDPE), High Density Polyethylene (HDPE) and Propylene (PP) to determine the effects of diirent packaging materials on shelf life of Capsicum annuum var. kulai. The effects of combined LDPE and MAP on shelf life of Capsicum annuum var. kulai were also evaluated. Results showed capsicum annuum var. kulai was fully developed between day 35 and day 42 after anthesis, but no significant changes in fresh weight from day 35 to day 42 after anthesis were recorded. Whist the dour of the fruits turned from breaker (day 35) to red (day 42). Pungency components such as capsaicin and dihydrocapsaicin reached maximum on day 42 after anthesis and began to decrease thereafter. Therefore, in order to maintain pungency components, the fruits should be harvested before day 42 of anthesis. Specific activity of degradative enzymes such as polygalacturonase (PG), pectin methylesterase (PME), a-D-mannosidase, p-D-galacturonase, cellulase and xylanase were identified at various stages of growing, maturation and ripening. PG activity which reached maximum at day 42 after anthesis was found to be relatively higher than PME and cellulase activity in capsicum annuum. Cellulase, xylanase, p-D-galacturonase and a-D-mannosidase activities did not show any effect in promoting softening of the fruit. Production of ethylene and COZ which are important during ripening of Capsicum annuum, increased fmm 4.54 to 12.24 pUhr/kg and 1.72 to 3.14 pUhr/kg respectively. Physical appearance of LDPE packaged Capsicum annuum did not change significantly until after 30 days of fruits storage. This was indicated by delay in shriveling, insignificant loss of fresh weight, firmness, absence of pedicel and calyx discdouration and decay. Study on firmness and freshness of capsicum showed no significant changes when stored under combined sealed LDPE bag for 30 days compared to perforated LDPE bag. It was also found that sealed LDPE bag was able to prolong fruit freshness which moisture loss was recorded less than 0.45% during the 30 days storage. Capsaicin and dihydrocapsaicin, which are important for pungency of the fruits, did not show any significant changes during the storage. In addition, physical appearance and natural nutrients of capsicum were maintained when packed in sealed LDPE bags. Results also indicated that sealed LDPE bag was found to be the best for extension of the storage life of Capsicum annuum var. kulai up to 30 days after harvesting at day 42 from anthesis.